Development of Student Worksheets Based on The Search, Solving, Create and Share (SSCS) Learning Model to Improve Critical Thinking Skills in Biology Learning for Third Level (XII) of Senior High School SMA Negeri 1 Pantai Labu - Desvica Simanullang; Ashar Hasairin Harahap; Martina Restuati (Universitas Labuhanbatu, 2024)
This project aims to (1) evaluated Student Worksheets (called as LKPD) based on Search, Solving, Create, and Share (SSCS) for material, design, and teacher response learning experts. (2) assess Search, Solving, Create, and Share (SSCS)-based Student Worksheets. This study used descriptive data analysis at SMAN 1 Pantai Labu. This Reserarch & Development follows Bord and Gall's development approach. The model has ten steps: research and information collection, planning, preliminary product development, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, and final product revision. In 2023, Third Level (XII) students at SMA Negeri 1 Pantai Labu tested the Student Worksheets, which was developed at Medan State University. A validation expert team-approved Student Worksheets is the product, based on Search, Solving, Create, and Share. The material expert team rated the Student Worksheets